Pro .NET Performance Optimize Your C# Applications - Goldshtein, Sasha; Zurbalev, Dima; Group, SELA; Flatow, Ido (Apress : Imprint: Apress, 2012)
Maximizing the performance of your algorithms and applications is extremely important and can give you a competitive advantage, a lower cost of ownership, and happier users. Pro .NET Performance explains the internals of Windows, the CLR, and the physical hardware that affect the performance of your applications, and gives you the knowledge and tools to measure how your code performs in isolation from external factors. The book is full of C# code samples and tips to help you squeeze every bit of juice from your application-lower memory utilization, consistent CPU usage, and fewer I/O operations across the network and disk. Pro .NET Performance will change the way you think about .NET application development. Guides you through performance measurement with a variety of profilers and other tools Explains how OS and CLR internals affect your application's performance in unexpected ways Provides you with tips and real-life case studies for improving application performance.